Increasing acetyl‐CoA metabolism attenuates injury and alters spinal cord lipid content in mice subjected to experimental autoimmune encephalomyelitis - Chevalier, Amber C.; Rosenberger, Thad A. (Journal of neurochemistry, 2017)
Acetate supplementation increases brain acetyl‐CoA metabolism, alters histone and non‐histone protein acetylation, increases brain energy reserves, and is anti‐inflammatory and neuroprotective in rat models of neuroinflammation and neuroborreliosis. To determine the impact acetate supplementation has on a mouse model of multiple sclerosis, we quantified the effect treatment had on injury progression, spinal cord lipid content, phospholipase levels, and myelin structure in mice subjected to experimental autoimmune encephalomyelitis (EAE). EAE was induced by inoculating mice with a myelin oligodendrocyte glycoprotein peptide fragment (MOG35–55), and acetate supplementation was maintained with 4 g/kg glyceryl triacetate by a daily oral gavage. Acetate supplementation prevented the onset of clinical signs in mice subject to EAE compared to control‐treated mice. Furthermore, acetate supplementation prevented the loss of spinal cord ethanolamine and choline glycerophospholipid and phosphatidylserine in mice subjected to EAE compared to EAE animals treated with water. Treatment increased saturated and monounsaturated fatty acid levels in phosphatidylserine compared to controls suggesting that acetate was utilized to increase spinal cord fatty acid content. Also, acetate supplementation prevented the loss of spinal cord cholesterol in EAE animals but did not change cholesteryl esters. Treatment significantly increased GD3 and GD1a ganglioside levels in EAE mice when compared to EAE mice treated with water. Treatment returned levels of phosphorylated and non‐phosphorylated cytosolic phospholipase A2 (cPLA2) levels back to baseline and based on FluoroMyelin™ histochemistry maintained myelin structural characteristics. Overall, these data suggest that acetate supplementation may modulate lipid metabolism in mice subjected to EAE. Experimental autoimmune encephalomyelitis (EAE) results in loss of lipid and demyelination by immune‐mediated mechanisms. In this study, we demonstrate that acetate supplementation attenuated the onset of clinical signs in EAE mice. Treatment prevented the loss of many spinal cord lipids, returned cytosolic phospholipase PLA2 to control levels, and maintained some myelin structural characteristics. Thus, treatment may reduce injury by altering lipid metabolism.